Ultra-broadband and wide-angle nonreciprocal thermal emitter based on Weyl semimetal metamaterials - Shi Kezhang; Sun Yuwei; Hu Run; He Sailing (Nanophotonics)
Nonreciprocal thermal radiation can violate Kirchhoff’s law and exhibit different emissivity at symmetric polar angles relative to the normal direction. Realizing a mid-infrared broadband nonreciprocal thermal emitter with a wide emission angle range is a fundamental yet challenging task, particularly without the need for an external magnetic field. Here, we propose a nonreciprocal thermal emitter operating in the mid-infrared that achieves a significantly nonreciprocal thermal radiation in a wavelength range from 12 μm to 20 μm, spanning a wide angular range from 16° to 88°. This is achieved by utilizing a multilayered Weyl semimetal (WSM)/dielectric structure, which takes the advantage of the strong nonreciprocity of WSMs with different Fermi levels and epsilon-near-zero-induced Brewster modes. The results provide a wider angular range in the broad mid-infrared band compared to previous attempts. The robustness of the nonreciprocal radiation is confirmed through wavelength-averaged emissivity across the azimuth angle φ range from 0° to 360°. Some possible materials and nanostructures as dielectric layers are discussed, showcasing the flexibility and reliability of the design. This work holds promising potential applications such as enhanced radiative cooling, thermal emitters for medical sensing and infrared heating, energy conversion, etc.